Unveiling Dynamic Changes of Chemical Constituents in Raw and Processed Fuzi With Different Steaming Time Points Using Desorption Electrospray Ionization Mass Spectrometry Imaging Combined With Metabolomics - Liu, Yue; Yang, Xuexin; Zhou, Chao; Wang, Zhang; Kuang, Tingting; Sun, Jiayi; Xu, Binjie; Meng, Xianli; Zhang, Yi; Tang, Ce (Frontiers in Pharmacology, 2022)
Fuzi is a famous toxic traditional herbal medicine, which has long been used for the treatment of various diseases in China and many other Asian countries because of its extraordinary pharmacological activities and high toxicity. Different processing methods to attenuate the toxicity of Fuzi is important for its clinical safe use. In this study, desorption electrospray ionization mass spectrometry imaging (DESI-MSI) with metabolomics combined-multivariate statistical analysis approach was applied to investigate a series of Aconitum alkaloids and explore potential metabolic markers to understand the differences between raw and processed Fuzi with different steaming time points. Moreover, the selected metabolic markers were visualized by DESI-MSI, and six index alkaloids’ contents were determined through HPLC. The results indicated visible differences among raw and processed Fuzi with different steaming times, and 4.0 h is the proper time for toxicity attenuation and efficacy reservation. A total of 42 metabolic markers were identified to discriminate raw Fuzi and those steamed for 4.0 and 8.0 h, which were clearly visualized in DESI-MSI. The transformation from diester-diterpenoid alkaloids to monoester-diterpenoid alkaloids then to non-esterified diterpene alkaloids through hydrolysis is the major toxicity attenuation process during steaming. DESI-MSI combined with metabolomics provides an efficient method to visualize the changeable rules and screen the metabolic markers of Aconitum alkaloids during steaming. The wide application of this technique could help to identify markers and reveal the possible chemical transition mechanism in the “Paozhi” processes of Fuzi. It also provides an efficient and easy way to quality control and ensure the safety of Fuzi and other toxic traditional Chinese medicine.